Analysis of Flouting Maxim in “Need for Speed (2014)” Movie - Fathol Dedy Susanto (Pioneer: Journal of Language and Literature, 2017)
This qualittaive research is about flouting maxim in Need for Speed movie. Flouting maxim was an action where the participants disobeyed the rule of cooperative principle in conversation. In this research, the researcher focused his research to analyze flouting maxims in Need for Speed movie and their effects in conversation. The research was conducted by accomodating one theory: flouting maxim by Herbert Paul Grice (1975). Grice’s theory determined flouting maxim as follow: flouting maxim of quantity, flouting maxim of quality, flouting maxim of relevant, flouting maxim of manner. Techniques of data collection: downloading Need for Speed movie, watching Need for Speed flouting maxim utterances. The finding of the data analysis showed that there were fifteen data found in Need for Speed movie. From the data, the researcher found flouting maxim of quality (four data), flouting maxim of quantity (two data), flouting maxim of relevant (seven data), and flouting maxim of manner (two data). In addition, the effects of flouting maxim are angry (five data), disappointed (one data), normal (four data), confusion (one data), offense (one data), surprised (one data), suspicious (one data), and disappointed (one data). The researcher expected the next researchers to conduct analysis on conversational maxim with other objectives of research. And different theories.